Pengaruh Risk Profile, Good Corporate Governance, Earnings, dan Capital Terhadap Financial Distress pada Unit Usaha Syariah Periode 2018-2022 - Gusniarti; Cindy Yuliana Harahap (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of RGEC (Risk Profile, Good Corporate Governance, Earning and Capital) on the financial distress of Sharia Business Units in Indonesia for the 2018-2022 period. The dependent variable in this research is financial distress and the independent variable is the ratios in the RGEC health assessment including NPF, FDR, GCG, BOPO, ROA, NIM, and CAR. The results of this research show that NPF, FDR, GCG, BOPO, ROA, NIM, and CAR. has a significant effect on the occurrence of financial distress in Indonesian Sharia Business Units for the 2018-2022 period.